The role of polymers in random lasing. Issue 14 (28th April 2015) - Sznitko, Lech; Mysliwiec, Jaroslaw; Miniewicz, Andrzej
ABSTRACT In this review article, we describe the basic principles of random laser operation with particular emphasis on π‐conjugated, dye‐doped and biologically inspired polymers. Random lasers are unusual types of lasers that use disorder in the light amplifying medium to provide positive feedback for laser operation. Organic systems like polymers are affected with disorder resulting both from their molecular structure and fabrication techniques. Due to this fact polymers seem to fit to role of random lasers and now are being extensively studied in this direction. Despite multiline and multidirectional operation polymeric random lasers have potential for several interesting applications. Here we show that they can be successfully applied to sensing in biology and medicine, encoding of information, display technology and search and rescue. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 951–974